Drosophila Models of Neurodegenerative Diseases - Lu, Bingwei (2009)
Neurodegenerative diseases are progressive disorders of the nervous system that affect specific cellular populations in the central and peripheral nervous systems. Although most cases are sporadic, genes associated with familial cases have been identified, thus enabling the development of animal models. Invertebrates such as Drosophila have recently emerged as model systems for studying mechanisms of neurodegeneration in several major neurodegenerative diseases. These models are also excellent in vivo systems for the testing of therapeutic compounds. Genetic studies using these animal models have provided novel insights into the disease process. We anticipate that further exploration of the animal models will further our understanding of mechanisms of neurodegeneration as well as facilitate the development of rational treatments for debilitating degenerative diseases.